Archaeology and Dams in Southeastern Turkey: Post-Flooding Damage Assessment and Safeguarding Strategies on Cultural Heritage - Marchetti, Nicolò; Bitelli, Gabriele; Franci, Francesca; Zaina, Federico (Journal of Mediterranean Archaeology, 2020)
The construction of dams is an ever-growing threat to cultural heritage, particularly in an age of climate change and narrowly focused development policies. In analyzing as a case study three major reservoirs in the Middle Euphrates river valley in southeastern Turkey (Atatürk, Birecik and Karkam??), we developed a Post-Flooding Damage Assessment (PFDA) to evaluate the impact of dams on archaeological sites. Our PFDA, consisting of an analysis of cross-correlations between multi-temporal Landsat imagery, geographical spatial datasets and archaeological data from surveys and excavations, provides an unprecedented detailed overview of the loss of especially significant cultural landscapes, and also highlights the limited accuracy of pre-flooding archaeological surveys and excavations. We conclude with recommendations for improving how rescue archaeological projects targeting endangered cultural landscapes are designed, with an immediately achievable target of better documenting cultural heritage threatened by dams.